Doppler echocardiographic characteristics of normal and dysfunctioning prosthetic valves in the tricuspid and mitral position. Issue 1 (January 1990) - Pye, M; Weerasana, N; Bain, W H; Hutton, I; Cobbe, S M
Abstract : The Doppler echocardiographic characteristics of 70 prosthetic valves in 35 patients are reported. Twenty nine patients had a Björk-Shiley prosthesis in both mitral and tricuspid positions and six had Carpentier-Edwards valves in both sites. Five of the patients had abnormal tricuspid prostheses on the basis of clinical and echocardiographic criteria. Pulsed wave Doppler echocardiography was used in all examinations. The pressure half times for the normal tricuspid prosthetic valves, 105 (40) ms (Björk-Shiley) and 97 (53) ms (Carpentier-Edwards), were significantly longer than those of normal mitral prosthetic valves, 75 (18) ms (Björk-Shiley) and 83 (15) ms (Carpentier-Edwards). The range of pressure half times for the abnormal tricuspid valves (237-530 ms) was distinct from that of the apparently normal tricuspid prosthetic valves (38-197 ms). There was an increase in the peak velocity of the obstructed tricuspid prosthetic valves (1.69 (0.12) m/s) in comparison with normal prostheses (1.06 (0.26) m/s). The normal range of pressure half times for the Björk-Shiley and Carpentier-Edwards valves in the mitral position is not applicable to the same valves in the tricuspid position. The valve appears to function well with very long pressure half times but a pressure half time of greater than 200 ms coupled with a peak velocity of greater than 1.60 ms without significant valve regurgitation indicates tricuspid obstruction of the tricuspid prosthetic valve.